2022
DOI: 10.1111/apa.16341
|View full text |Cite
|
Sign up to set email alerts
|

Predicting factors of clinically significant urological anomalies after initial urinary tract infection among 2‐ to 24‐month‐old children

Abstract: Aim: To find more effective criteria to identify clinically significant urological anomalies after initial urinary tract infection among children. Methods:Children aged 2-24 months with an initial urinary tract infection were consecutively recruited in a Japanese hospital from 2013 to 2019. Voiding cystourethrography, 99mTc dimercaptosuccinic acid scan and ultrasound were intended to perform for all cases. Clinically significant urological anomalies were defined as high-grade vesicoureteral reflux, obstructive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The purposes of UTI in childhood often consist of eradication of the bacterial pathogen, identification of CAKUT, and avoidance of recurrent infections. 10 Prompt diagnosis and appropriate treatment are very important for children to reduce the morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…The purposes of UTI in childhood often consist of eradication of the bacterial pathogen, identification of CAKUT, and avoidance of recurrent infections. 10 Prompt diagnosis and appropriate treatment are very important for children to reduce the morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…Another parameter strongly related to malformations is infection with a non‐ E. coli pathogen 10,11,21 . In our study, having an infection with an atypical pathogen increased the probability of underlying malformations by four times.…”
Section: Discussionmentioning
confidence: 48%
“…19 Different studies have identified various risk factors associated with NUM, and some heterogeneous recommendations have been made based on these criteria. 10,11,20,21 However, until now, there has yet to be a predictive model with good predictive capacity, based solely on clinical and analytical parameters, capable of stratifying patients into risk groups for individualised imaging protocols.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations